The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3802/jgo.2013.24.3.258
|View full text |Cite
|
Sign up to set email alerts
|

The combination of intravenous bevacizumab and metronomic oral cyclophosphamide is an effective regimen for platinum-resistant recurrent ovarian cancer

Abstract: ObjectiveTo determine the efficacy, progression-free survival (PFS) and overall survival (OS) for the combination of intravenous bevacizumab and oral cyclophosphamide in heavily pretreated patients with recurrent ovarian carcinoma.MethodsA retrospective review was performed for all patients with recurrent ovarian carcinoma treated with intravenous bevacizumab 10 mg/kg every 14 days and oral cyclophosphamide 50 mg daily between January 2006 and December 2010. Response to treatment was determined by Response Eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…Over the past decade, a new paradigm has emerged in the pharmacological treatment of neoplastic disease termed "metronomic chemotherapy," which involves the frequent administration of chemotherapeutic drugs at concentrations [3][4][5][6][7][8][9][10] times below the established MTD without breaks in dosing schedule for prolonged periods of time. For example, by using a dosing schedule of cyclophosphamide in the murine lung cancer and leukemia models that provided more sustained apoptosis of endothelial cells within the vascular bed of a tumor, it was shown that a chemotherapeutic agent can more effectively control tumor growth in mice, regardless of whether the tumor cells are drug resistant [3].…”
Section: Metronomic Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, a new paradigm has emerged in the pharmacological treatment of neoplastic disease termed "metronomic chemotherapy," which involves the frequent administration of chemotherapeutic drugs at concentrations [3][4][5][6][7][8][9][10] times below the established MTD without breaks in dosing schedule for prolonged periods of time. For example, by using a dosing schedule of cyclophosphamide in the murine lung cancer and leukemia models that provided more sustained apoptosis of endothelial cells within the vascular bed of a tumor, it was shown that a chemotherapeutic agent can more effectively control tumor growth in mice, regardless of whether the tumor cells are drug resistant [3].…”
Section: Metronomic Chemotherapymentioning
confidence: 99%
“…As opposed to targeting rapidly-dividing tumor cells with MTD therapy, metronomic therapy regimens primarily exert their effects on the vascular endothelial cells of the tumor, which are more sensitive to low concentrations of chemotherapeutic drugs than normal host or tumor cells [7]. When combined with angiogenesis inhibitors such as Bevacizumab (Avastin®, a recombinant humanized monoclonal antibody that neutralizes the biological activity of human VEGF), metronomic chemotherapy may have significant clinical utility even in drug-resistant cancers [8]. However, it is important to note that tumor endothelial cells (TEC) quite differ from normal endothelial cells in many parameters, including cell proliferation, migration, gene profile and responses to growth factors and several chemotherapeutic drugs [9].…”
Section: Metronomic Chemotherapymentioning
confidence: 99%
“…Metronomic therapy, a continuous frequent administration of anticancer agents at a minimally effective dose without prolonged drug‐free breaks, has been intensively studied in clinical trials as an alternative of MTD therapy . Indeed, many clinical studies reported that metronomic therapy displayed lower toxicity than MTD despite similar efficacy, improved progression‐free survival and overall survival of the patients . Therefore, metronomic dosing is considered to be more suitable for long‐term management of cancer patients than MTD.…”
mentioning
confidence: 99%
“…Overall, bevacizumab is the first biological therapy to have shown efficacy in ovarian cancer and to obtain approval in certain countries. In this issue, Barber et al [5] reported 42.4% of an impressive overall response rate, including 10.6% of complete response rate in 66 patients with heavily pre-treated recurrent platinum-resistant ovarian cancer when they were offered a combination of bevacizumab and oral metronomic cyclophosphamide (OMC). Despite this remarkable tumor shrinkage activity, the median PFS remained relatively short, between 3 months for the whole population and 5 months for the responders.…”
mentioning
confidence: 99%
“…However, it might be due to the time in the disease evolution when the combination was administered. In the trial run by Garcia et al [10], patients had received a maximum of 3 prior regimens in contrast to a median 6.5 in the series of Barber et al [5]. It has been noticed that the hazard ratio of bevacizumab activity in combination with chemotherapy followed by maintenance may be different according to the disease setting, suggesting a higher efficacy of bevacizumab in relapse than in first-line.…”
mentioning
confidence: 99%